2014
DOI: 10.1051/matecconf/20141415002
|View full text |Cite
|
Sign up to set email alerts
|

Creep behavior of a novel Co-Al-W-base single crystal alloy containing Ta and Ti at 982C

Abstract: Abstract. The tensile creep behavior of a Co-Al-W-base single crystal alloy containing Ta and Ti was investigated at 982 • C and 248 MPa. The lattice misfit of experimental alloy was measured to be positive by synchrotron X-ray diffraction at high temperature, and long term heat treatment at 1000 • C for 1000 h revealed a γ volume fraction of 75% without secondary phases. The creep test indicated that the creep properties of experimental alloy exceeded commercial 1st generation Ni-base single crystal superallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In general, both Co-base and Co-Nibase alloys show properties comparable to or better than those of first-generation Ni-base single crystals. The alloys with the lowest creep rates across this temperature range are in general Tiand/or Ta-containing compositions (50,57,58). Co-Ni-base alloys also demonstrate favorable creep properties.…”
Section: Figure 10mentioning
confidence: 90%
See 2 more Smart Citations
“…In general, both Co-base and Co-Nibase alloys show properties comparable to or better than those of first-generation Ni-base single crystals. The alloys with the lowest creep rates across this temperature range are in general Tiand/or Ta-containing compositions (50,57,58). Co-Ni-base alloys also demonstrate favorable creep properties.…”
Section: Figure 10mentioning
confidence: 90%
“…Creep ductilities are overall somewhat higher in Co-Ni-based alloys, exceeding 25% across a range of compositions (50). Figure 12b compares the creep properties of single crystals of Co-base and Co-Ni-base alloys (50,51,(56)(57)(58) in comparison to Ni-base single crystals of René N4 (52). In general, both Co-base and Co-Nibase alloys show properties comparable to or better than those of first-generation Ni-base single crystals.…”
Section: Figure 10mentioning
confidence: 96%
See 1 more Smart Citation
“…THE recent report of a c¢-strengthened Co-Al-Wbased alloy opened up a practical possibility for developing new Co-based superalloys, which have become an increasingly active research area over the past decade. [1][2][3][4][5][6][7][8][9][10][11][12][13] After studying their potentials, it was found that the solvus temperature of c¢ precipitates can be increased up to 1200°C with high solidus temperature, [2][3][4][5] mechanical performance [6][7][8] and oxidation properties [9][10][11][12][13] as promising engineering materials candidate for high-temperature applications. However, their high density and limited microstructural stability remain the biggest challenges for their further development.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still no clear conclusion on the mechanism of the influence of Co on the microstructure stability of superalloys. Thirdly, Co improves the creep properties of superalloys by reducing the stacking-fault energy of γ matrix [15][16][17]. The stacking-fault energy significantly influences the creep process due to the climb and cross slip of the dislocations in γ matrix or the introduction of more twin structures in superalloy [6].…”
Section: Introductionmentioning
confidence: 99%